Dysregulation of miR-31 and miR-375 expression is associated with clinical outcomes in oral carcinoma - Siow, M.Y.; Ng, L.P.K.; Chong, V.K.V.; Jamaludin, M.; Abraham, M.T.; Rahman, Z.A.A.; Kallarakkal, T.G.; Yang, Y.H.; Cheong, S.C.; Zain, R.B. (Blackwell Publishing, 2014)

(untitled)
Objectives To identify differentially expressed miRNA between oral squamous cell carcinoma (OSCC) and non-cancer (NC) and to associate these with clinico-pathological parameters. Materials and methods miRNA microarray profiling was utilized to obtain the expression profile of miRNAs in four OSCC and four NC samples. The expression of miR-31 and miR-375 was further validated in 26 OSCC and three NC samples using real-time-PCR. The association between miRNA expression and clinico-pathological parameters was tested by univariate and multivariate analyses. Results